How to solve 3x + 12 = -6? Get the answer and stepwise instruction to solve linear equation in one variable 𝒙.

#### Steps for finding the solution

We have 3**x** + 12 = -6

First, we move the *non ***x** terms to the RHS of the equation. To do this, we subtract 12 from both sides.

**Note: ** if a = b, then a - c = b - c

Therefore, 3**x** + 12 - 12 = -6 - 12

or, 3**x** = -18

Next, divide both sides by 3, which is the coefficent of **x**

**Note: ** if a = b, then a ÷ c = b ÷ c

3**x**/3 = -18/3

**x** = -18/3

To simplify, divide both numerator and denominator by 3, which is the GCF of 18 and 3:

**x** = -6/1 or, **x** = -6